The Effects of Endoscopy-Guided Nasojejunal Feeding Tube Placement in Post-COVID-19 ICU Patients: A Retrospective Study - Chen Y; Wu G; Qu C; Ye Z; Kang Y; Tian X (International Journal of General Medicine)
Yuequn Chen, Guiqiong Wu, Chaojun Qu, Zimao Ye, Yihao Kang, Xin Tian Department of Intensive Care Unit, Fifth Affiliated Hospital of Wenzhou Medical University; Lishui Municipal Central Hospital, Lishui, 323000, People’s Republic of ChinaCorrespondence: Xin Tian, Department of Intensive care unit, Fifth Affiliated Hospital of Wenzhou Medical University; Lishui Municipal Central Hospital, No. 289, Kuocang Road, Liandu District, Lishui, 323000, People’s Republic of China, Tel +86-0578-2285301, Email zjlstx@126.comBackground: The impact of complications and long-term outcomes remains unclear for endoscopy-guided nasojejunal feeding tube (ENFT) placement versus blind nasogastric feeding tube (BNFT) placement on post-COVID-19 ICU patients.Study Design: A retrospective cohort study comparing BNFT and ENFT placement in ICU patients post-COVID-19 infection.Objective: To evaluate the impact of BNFT versus ENFT placement methods on complications in post-COVID-19 ICU patients requiring enteral feeding.Participants: A total of 310 ICU patients were retrospectively analyzed after applying inclusion and exclusion criteria, comprising 99 patients in the ENFT group and 211 patients in the BNFT group.Setting: The study was conducted in the intensive care units of a tertiary care hospital from September 2023 to November 2023.Outcome Measures: Primary outcomes included baseline clinical characteristics and symptoms prior to COVID-19 infection. Secondary outcomes assessed post-COVID-19 complications over short (up to 2 weeks), medium (2– 4 weeks), and long-term (beyond 4 weeks) periods. These complications included shortness of breath, cognitive dysfunction, muscle and joint pain, sleep disturbances, and gastrointestinal symptoms, measured by GSRS and SAQ scores.Results: Baseline characteristics were similar between both groups (p > 0.05), indicating well-matched cohorts. Post-COVID-19, the ENFT group exhibited significantly lower rates of shortness of breath, cognitive dysfunction, muscle and joint pain, sleep disturbances, and mental health challenges, especially for long-term feeding tube usage (p < 0.05). GSRS scores were lower and SAQ scores were higher in the ENFT group, indicating better gastrointestinal and cardiovascular outcomes.Conclusion: ENFT placement is associated with fewer post-COVID-19 complications compared to BNFT, particularly for patients requiring long-term feeding tube usage in the ICU.Keywords: nasojejunal tube placement, prone ventilation, post-COVID-19 ICU patients, safety, enteral feeding